Beyond the Trenches - The Social and Cultural Impact of the Great War (2017)
This collection of articles is the outcome of extensive investigations into archival materials, concerning the involvement of various nations in the Great War. The authors analyse the wartime experiences of individuals and local communities, as well as whole nations. They offer a closer, more personal view of the impact of the Great War. The book re-constructs individual war narratives, and studies the long-term consequences of the conflict. The result is a multifaceted portrayal of the war, seen from local and international perspectives.